Effects of Dietary Poly-β-Hydroxybutyrate Supplementation on the Growth, Non-specific Immunity, and Intestinal Microbiota of the Sea Cucumber Apostichopus japonicus - Liu, Longzhen; Wang, Mingyang; Wei, Cong; Liu, Yang; Pan, Miaojun; Wang, Shishuang; Cui, Liang; Tian, Xiangli (Frontiers in Marine Science, 2022)
The present study evaluated the effects of dietary supplementation with poly-β-hydroxybutyrate (PHB) on the growth performance, non-specific immunity, immune-related genes expression in the NF-κB signaling pathway, and intestinal microbiota of sea cucumber Apostichopus japonicus. During a 63-day feeding trial, sea cucumber was fed with basal diet (control, C treatment) and treatment diets supplemented at different doses of PHB, i.e., 0.5% (P treatment), 1% (OP treatment) and 3% PHB (TP treatment) (w/w) followed by a stimulation test of inactivated Vibrio splendidus for seven days. All PHB treatments significantly promoted the specific growth rate and weight gain rate of sea cucumber (P < 0.05). The 1% PHB significantly enhanced phagocytic, respiratory burst, superoxide dismutase, alkaline phosphatase, acid phosphatase, catalase, and lysozyme activities in the coelomocytes of A. japonicus (P < 0.05). However, no elevated activities of catalase and lysozyme were observed in the P treatment (P < 0.05), and only increased catalase activity appeared in TP treatment (P < 0.05). Quantitative real-time PCR revealed significantly higher expression levels of Aj-p105, Aj-p50, and Aj-rel in the mid-intestine tissue of sea cucumber in PHB treatments (P < 0.05), and the relative expression level Aj-lys gene was significantly higher in OP treatment (P < 0.05) than that in the control. After injection of inactivated V. splendidus, the relative expression level of four immune-related genes in the OP treatment were significantly up-regulated at 24 h (P < 0.05). The richness of intestinal microbiota in PHB treatments significantly increased, while diversity in TP treatment significantly decreased (P < 0.05). The relative abundances of Rhodobacteraceae in PHB treatments were significantly higher than that in the control (P < 0.05). Network analysis revealed that 0.5% and 1% PHB supplement enhanced the stability of the intestinal microbial ecosystem. Functional predicted revealed that PHB diet significantly increased some potential functions of intestinal microbiota, involving amino acid, lipid, and nucleotide metabolisms. In summary, dietary supplementation with a suitable dose of PHB had shown multiple beneficial effects on A. japonicus. Considering collectively the above, the optimum dose of 1% PHB addition to the diet of A. japonicus is recommended.